Perancangan DFD Berdasarkan Hasil Pengukuran Kualitas Website Melalui Metode Webqual4.0 Pada jd.id - Kanji Prasetiyo; Yudi Priyadi (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2018)
Currently JD.id website entered into five e-commerce website with the highest number of visitors in Indonesia, and no previous research that measures the level of quality of JD.id website. Measuring the quality of a website is useful to assess the overall e-commerce website based on consumer perceptions. This study aims to measure website quality using webqual 4.0 method based on user satisfaction variable with case study of JD.id website. Data Flow Diagram model is used to make system model recommendation design, while method of webqual 4.0 is used to measure website quality to user satisfaction. Research data in the form of questionnaires involving 384 respondents who had transacted on JD.id website. Data analysis techniques use descriptive statistics. Based on the results of research on the quality of JD.id website, simultaneously have a positive and significant impact on user satisfaction JD.id website. The result of partial test shows that three variables partially have a positive influence on user satisfaction JD.id website that is usability quality, information quality, and service interaction quality, with service interaction quality variable has the biggest influence. Therefore, system modeling using Context Diagram (CD) and Data Flow Diagram (DFD) focuses on service interaction quality variable with the addition of new entity that is CS Complain along with its process include procedure, processed complaint, and solution. Besides, there are also Data store Detail complaint.